Estimation of asymptotic spermatocrit value of bovine semen - CHAKRABARTI, DEBDATTA (The Indian Journal of Animal Sciences, 2013)
Rationalisation of method for determining spermatocrit value at an arbitrarily chosen speed of centrifugation is attempted through determination of asymptotic spermatocril value which represents the final volume of packing under increasing relative centrifugal force. Asymptotic spermatocnt value of 56 ejaculates from 3 different breeds of bulls is estimated as 3.047Â±2.3316 (mean Â±SD). High coefficient of variation is due to the wide variation in the spenn density of the samples. The asymptotic sperrnatocrit value would radically help in easy determination of total count, mean corpuscular volume and density for belter understanding of physiological qualities of the sperm cells in the sample.